PENGARUH LATIHAN PERMAINAN TERARAH TERHADAP KEMAMPUAN MENGOPER DAN MENGHENTIKAN BOLA PERMAINAN SEPAKBOLA SISWA SMA NEGERI 1 PERANAP - Yoga pratama; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : the purpose of this study to determine the effect of exercise games focus on the ability to pass and stop the soccer game ball SMA Negeri 1 Peranap. This type of research taking approach one-group pretest-posttest design. The population in this study were students SMA N 1 Peranap consisting of 18 people. The sampling technique in this research is a full sampling, namely the determination of the sample when all members of the population used as a sample. Data analysis using statistical t-test. Results of analysis showed that there are significant game exercises focused on the ability to pass the ball and stop the high school football games N 1 Peranap, from an average of 17.61 into 21.33 in the final test with a mean difference of 3.72 (taccount 16.484 and ttabe1 1.740).Keywords : Directed game, pass, Stopping Ball, Football